Pengembangan Digital Art sebagai Asset Video Game Moral Edukasi menggunakan RND - Jaslina, Jaslina; Wibowo, Tony (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2024)
One of the forms produced by digital images is Digital Art: the artwork thatwas created using digital technology or a computer. Digital art has becomean important element in video game development. The uniqueness of avideo game, aesthetically, depends on digital art usage as a game asset, suchas for the avatar of the video game character used. In the development ofeducational video game prototypes with moral topics aimed at Indonesianhigh school students, digital art that displays diverse cultural and ethniccharacteristics is needed so that the delivery of the material presented isimmersive to players. This study uses the RND approach, where theResearch approach uses qualitative methods in the form of observing the physical characteristics of each ethnic group and the Development approachuses the PDDIE (Planning, Design, Development, Implementation,Evaluation) method. The results of the design and development of digitalart are then applied in educational moral video games as character assets.The application of digital art as a moral education video game design assetto students makes learning more immersive and enjoyable.